2005
DOI: 10.1002/ijc.21099
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and temporal variations in cancer of the corpus uteri: Incidence and mortality in pre- and postmenopausal women in Europe

Abstract: Corpus uteri cancer is the fourth most common neoplasm in women in Europe and the tenth most common cause of cancer death. We examined geographic and temporal variations in corpus uteri cancer incidence and mortality rates in the age groups 25-49 and 50-74 in 22 European countries. The disease is considerably less common in premenopausal women, with incidence and mortality rates decreasing throughout Europe and mortality declines more marked in western and southern European countries. Incidence rates among pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 45 publications
2
58
0
4
Order By: Relevance
“…Endometrial cancer is the most common gynecological malignancy in the western world and the incidence is rising in several countries (1). 15% to 20% of patients with presumed localized disease at primary treatment recur (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Endometrial cancer is the most common gynecological malignancy in the western world and the incidence is rising in several countries (1). 15% to 20% of patients with presumed localized disease at primary treatment recur (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported relevant proportions of unspecified uterine cancer deaths or addressed the need of correcting estimates for cervical and corpus uteri cancer (6)(7)(8)(9)(10)(11)(12)(13)(23)(24)(25)(26)(27)(28)(29)39,40). The current assessment of different strategies to perform this correction indicated important modifications of the epidemiologic profile of cervix and corpus uteri cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The partial correction represents a conservative option which considers that at least some of the deaths formerly classified as uterus NOS should remain unspecified as to the affected tissue. Although a further estimating process is subject to a higher risk of error, the full correction has been applied to several recent studies on uterine cancer mortality (10,23,40). In spite of the longstanding call for increased accuracy of the report of deaths by uterine cancer (7), the proportion of unspecified mortality remains high in the Brazilian context.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial cancer is one of the most prevalent malignant tumors of the female genital tract, accounting for 6% of all cases of cancer in women (1). According to the American Cancer Society, the annual incidence of endometrial cancer is increasing, with ~40,880 new cases diagnosed in the USA in 2005 (2) and ~49,560 new cases in 2013 (3).…”
Section: Introductionmentioning
confidence: 99%